Evaluation of spinal injuries by MRI - Bollipo, Johny Prasad; Rao, Pasupuleti Bhimeswara (International Surgery Journal, 2019)
Background: Radio-imaging is one of the most important tools in the diagnosis of spinal injury and helps to start a prompt and correct treatment to patients. Compared to CT, MRI allows better visualization of various tissues, including spinal cord and ligaments, not to mention discs and vessels. This study was done to evaluate the efficacy of low tesla MRI in acute spinal injuries. Methods: Site of injury, neurological status of the patient etc., were noted from 78 patients included in the study. The neurological status was evaluated according to the American Spinal Injury Association Impairment Scale. Within 2days of admission, MRI was done. In case of doubt, radiographs for superior and articular processes was done where necessary. CT was done in case edema was seen without a fracture line. Results: Most of the patients were males with the maximum of the patients being between the ages 21-50 years. Fall from height was the most common cause of injury and cervical region was the most common site. Osseous injury, ligament disruption and spinal cord injury were the most common MRI findings. Conclusions: Being non-invasive procedure with high specificity and sensitivity, MRI is a preferred diagnostic tool to assess the spinal cord injuries.